Ordinance No. 79: An Ordinance Relating to Crimes and Punishments, in Scandia Journal, Jan. 5, 1894, at 8, § 11 - (:unkn) unknown (My University, 1894)
§ 11: Every person who shall, within the corporate limits of the city of Scandia, discharge any firearm, rocket, giant powder, fireworks, or any other explosive material without first obtaining a permit from the mayor shall be fined twenty five dollars upon conviction
Keywords: DISCHARGE